2003
DOI: 10.1111/1467-8276.00136
|View full text |Cite
|
Sign up to set email alerts
|

Willingness to Pay for Curbside Recycling with Detection and Mitigation of Hypothetical Bias

Abstract: In this article, we estimate willingness to pay for curbside recycling. Using a unique data set, we also test for and detect significant hypothetical bias using stated-and revealed-preference data. A shortscripted "cheap-talk" statement is used to mitigate the bias and provide more efficient estimates of the welfare impacts of curbside recycling programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
100
3

Year Published

2005
2005
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 150 publications
(110 citation statements)
references
References 29 publications
(11 reference statements)
7
100
3
Order By: Relevance
“…7 Both List (2001), who used the full (Cummings and Taylor 1999) script in a second-price auction for a private good, and Lusk (2003), who used a shorter but largely similar script in a dichotomous choice mail survey valuing a private good, found that cheap talk lowered bids for inexperienced consumers but not for experienced ones. Aadland and Caplan (2003), using a very short script in a phone survey, also found evidence that people differ in their susceptibility to cheap talk. Murphy et al (2005b), using the full script in an experiment eliciting individual donations subject to a provision point, found that cheap talk was quite effective at reducing hypothetical bias at bid levels of $9 and higher but less effective at lower bid levels.…”
mentioning
confidence: 92%
“…7 Both List (2001), who used the full (Cummings and Taylor 1999) script in a second-price auction for a private good, and Lusk (2003), who used a shorter but largely similar script in a dichotomous choice mail survey valuing a private good, found that cheap talk lowered bids for inexperienced consumers but not for experienced ones. Aadland and Caplan (2003), using a very short script in a phone survey, also found evidence that people differ in their susceptibility to cheap talk. Murphy et al (2005b), using the full script in an experiment eliciting individual donations subject to a provision point, found that cheap talk was quite effective at reducing hypothetical bias at bid levels of $9 and higher but less effective at lower bid levels.…”
mentioning
confidence: 92%
“…The underlying idea of the script is that, by raising the issue in the survey, respondents would not want to be part of such an ill-behaved group and would be less prone to hypothetical bias. The effect of the cheap talk script is varied and, among other factors, its success seems to depend on the characteristics of the good, the length of the script, and the valuation method (see Aadland andCaplan 2003, 2006;Carlsson et al, 2005;Cummings and Taylor, 1999;List, 2001;and Murphy et al, 2005). Given these limitations, it is too optimistic to expect cheap talk to completely mitigate hypothetical bias.…”
Section: Introductionmentioning
confidence: 99%
“…The cheap talk approach (Cummings and Taylor 1999), for example, is a popular calibration technique in which the hypothetical bias problem is described to subjects. Yet, the effectiveness of this approach may be sensitive to key variables such as script length (Poe et al 2002;Aadland and Caplan 2003), subject experience (List 2001;Lusk 2003;Aadland and Caplan 2003) and payment amounts (Brown et al 2003;Murphy et al 2005b). In fact, Aadland and Caplan (2006) find that a neutral cheap talk script can actually exacerbate hypothetical bias.…”
mentioning
confidence: 99%